The multistage crystallization of zircon in calc-alkaline granitoids : U-Pb age constraints on the timing of Variscan tectonic activity in SW Iberia - Pereira, M. F. (2016)
CL imaging and U–Th–Pb data for a population of zircons from two of the Évora Massif granitoids (Ossa-Morena Zone, SW Iberia) show that both calc-alkaline granitoids have zircon populations dominated by grains with cores and rims either showing or not showing differences in Th/U ratio, and having ages in the range ca. 350–335 Ma (Early Carboniferous). Multistage crystallization of zircon is revealed in two main growth stages (ca. 344–342 Ma and ca. 336–335 Ma), well represented by morphologically complex zircons with cores and rims with different ages and different Th/U ratios that can be explained by: (1) crystallization from melts with different compositions (felsic peraluminous to felsic-intermediate metaluminous; 0.001 Th/U ratio < 0.5) and (2) transient temperature fluctuations in a system where anatectic felsic melts periodically underwent injection of more mafic magmas at higher temperatures. The two studied calc-alkaline granitoids do not include inherited zircons (pre-Carboniferous), probably because they were formed at the highest grade of metamorphism (T 837 °C; granulite facies) and/or because they were derived from inheritance-poor felsic and mafic rocks from a previous cycle, as suggested by the internal structures of zircon cores. These Variscan magmatic rocks with crystallization ages estimated at ca. 336–335 Ma are spatially and temporally related to high-temperature metamorphism, anatexis, processes of interaction between crustal- and mantle-derived magmas and intra-orogenic extension that acted in SW Iberia during the Early Carboniferous.